A cross-country comparison of climate change in middle school science and geography curricula. Issue 9 (13th June 2022) - Dawson, Vaille; Eilam, Efrat; Tolppanen, Sakari; Assaraf, Orit Ben Zvi; Gokpinar, Tuba; Goldman, Daphne; Putri, Gusti Agung Paramitha Eka; Subiantoro, Agung Wijaya; White, Peta; Widdop Quinton, Helen
ABSTRACT: The challenge of climate change means that school education is more important than ever in preparing young people for an uncertain future. The focus of this research is climate change education and its status in the compulsory middle school years (approximately years 7–10) across six countries (Australia, Israel, Finland, Indonesia, Canada and England). The authors investigated formal published national curriculum documents, specifically science and geography, to determine the presence of climate change topics, and the way they are addressed in these subjects. The key findings are that: (1) the term 'climate change' appears in the formal curriculum of all six countries in science or geography; (2) approaches to climate change in the curriculum differ substantially across different countries; (3) climate change is often presented as a context, example or elaboration for other science concepts rather than a discrete topic; (4) the presence of climate change in most curriculum documents is scattered and spread over multiple years and (5) knowledge about causes of climate change predominates over action and behavioural changes. These findings raise questions as to whether current school curricula provide sufficient guidance for teachers to develop students' understandings, skills and values regarding climate change.